Effect of Size of Polyester Matrix Coconut Coir Powder on Bending Test and Scanning Electron Microscopy (SEM) Test - Asep Romi Ramadhan; Gugun Gundara; Acep Wagiman (R.E.M. (Rekayasa Energi Manufaktur) Jurnal, 2023)
Coconut plants are plants that are often found in all corners of the archipelago, so that natural products in the form of coconut in Indonesia are very abundant. Coconut fiber waste has the potential to be used as a reinforcement for new materials in composites. Coconut coir contains fiber which is an alternative natural fiber material in the manufacture of composites. The purpose of this study was to determine the effect of coco coir powder size on mechanical properties (bending test and SEM test) with coco coir powder size of 20, 40, 60 mesh with a volume fraction of 30% and following the ASTM D 790-03 composite material standard. SEM testing was carried out to determine differences in the surface conditions of the specimen due to fracture and the manufacturing process using the hand lay up method, SEM photos were used to analyze the morphology of the coconut powder composite with a polyester matrix. The results of the ASTM D 790-03 bending test resulted in the average bending strength values, namely 86,81 MPa resin specimens, 49,06 MPa 20 mesh specimens, 48,42 Mpa 40 mesh specimens, 45,44 Mpa 60 mesh specimens. The results of the SEM photo show that the powder is not completely bonded, so there are still voids and cracks in the empty matrix area, this can be caused by air trapping in the composite during molding.